Evaluation of Polymorphisms in Toll-Like Receptor Genes as Biomarkers of the Response to Treatment of Erythema Nodosum Leprosum - Maciel-Fiuza, Miriãn Ferrão; Costa, Perpétua do Socorro Silva; Kowalski, Thayne Woycinck; Schuler-Faccini, Lavínia; Bonamigo, Renan Rangel; Vetoratto, Rodrigo; Eidt, Letícia Maria; de Moraes, Paulo Cezar; Silveira, Maria Irismar da Silva; Camargo, Luis Marcelo Aranha; Callegari-Jacques, Sidia Maria; Castro, Stela Maris de Jezus; et al. (Frontiers in Medicine, 2022)
Erythema nodosum leprosum (ENL) is an inflammatory complication caused by a dysregulated immune response to Mycobacterium leprae. Some Toll-like receptors (TLRs) have been identified as capable of recognizing antigens from M. leprae, triggering a wide antimicrobial and inflammatory response. Genetic polymorphisms in these receptors could influence in the appearance of ENL as well as in its treatment. Thus, the objective of this work was to evaluate the association of genetic variants of TLRs genes with the response to treatment of ENL with thalidomide and prednisone. A total of 162 ENL patients were recruited from different regions of Brazil and clinical information was collected from their medical records. Genomic DNA was isolated from blood and saliva samples and genetic variants in TLR1 (rs4833095), TLR2 (rs3804099), TLR4 (rs1927914), and TLR6 (rs5743810) genes were genotyped by TaqMan real-time PCR system. In order to evaluate the variants’ association with the dose of the medications used during the treatment, we applied the Generalized Estimating Equations (GEE) analysis. In the present sample, 123 (75.9%) patients were men and 86 (53.1%) were in treatment for leprosy during the ENL episode. We found an association between polymorphisms in TLR1/rs4833095, TLR2/rs3804099, TLR4/rs1927914, and TLR6/rs5783810 with the dose variation of thalidomide in a time-dependent manner, i.e., the association with the genetic variant and the dose of the drug was different depending on the moment of the treatment evaluated. In addition, we identified that the association of polymorphisms in TLR1/rs4833095, TLR2/rs3804099 and TLR6/rs5783810 with the dose variation of prednisone also were time-dependent. Despite these associations, in all the interactions found, the influence of genetic variants on dose variation was not clinically relevant for therapeutic changes. The results obtained in this study show that TLRs polymorphism might play a role in the response to ENL treatment, however, in this context, they could not be considered as useful biomarkers in the clinical setting due small differences in medication doses. A larger sample size with patients with a more genetic profile is fundamental in order to estimate the association of genetic variants with the treatment of ENL and their clinical significance.